2020
DOI: 10.1002/art.41284
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Occupancy Profiling Reveals Critical Roles of FoxO1 in Regulating Extracellular Matrix and Circadian Rhythm Genes in Human Chondrocytes

Abstract: Objective Osteoarthritis (OA) is the most common age‐related joint disease. With aging and in OA, the expression of FoxO transcription factors is reduced, diminishing their chondroprotective actions. In order to elucidate the molecular mechanisms by which FoxO1 protects chondrocytes, we sought to identify the genome‐wide occupancy profile of FoxO1. Methods We performed FoxO1 chromatin immunoprecipitation followed by high‐throughput sequencing (ChIP‐Seq) on human primary chondrocytes. ChIP‐Seq data were integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Expression of collagen, a major component of ECM, is substantially upregulated in the subclinical and clinical phases of AD, which is associated with increased A β deposition [ 100 ]. In addition, our enrichment analysis has clarified that FOXO1 is associated with the regulation of ECM-receptor interaction pathway, in line with evidence of osteoarthritis for the involvement of aberrant FOXO1 expression in ECM-receptor interaction pathway [ 101 ].…”
Section: Discussionsupporting
confidence: 70%
“…Expression of collagen, a major component of ECM, is substantially upregulated in the subclinical and clinical phases of AD, which is associated with increased A β deposition [ 100 ]. In addition, our enrichment analysis has clarified that FOXO1 is associated with the regulation of ECM-receptor interaction pathway, in line with evidence of osteoarthritis for the involvement of aberrant FOXO1 expression in ECM-receptor interaction pathway [ 101 ].…”
Section: Discussionsupporting
confidence: 70%
“…FoxO transcription factors could regulate various cellular processes, including cell cycle regulation, redox balance, autophagy, apoptosis, metabolism, and repair of DNA damage [ 29 , 33 , 34 ]. FoxO is an important regulator of cartilage homeostasis and involved in the formation, development, and maturation of cartilage [ 35 , 36 ]. Akasaki et al found the various expressions of FoxO in the cartilage of mice of different ages and different months [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It regulates the gene expression of ACAN and COL2A1 ( Fig. 6(b) ) ( 50 ) . TNFAIP6 is an anti-inflammatory protein that is induced by TNF-α cytokine.…”
Section: Discussionmentioning
confidence: 99%